ANALISIS TEBAL PERKERASAN JALAN LINGKAR PERKANTORAN GERBANG 1 – GERBANG 2 KABUPATEN BANYUASIN MENGGUNAKAN METODE MDP 2013 - Indrayani Indrayani; Norca Praditya (FROPIL (Forum Profesional Teknik Sipil), 2020)
The Banyuasin Regency office ring road is one of the arterial roads in Banyuasin Regency. This road has an LHR in 2020 of 756. The results of the road condition survey show that the road conditions are damaged, cracks, holes, and loose asphalt. Therefore, the pavement thickness planning is carried out again or overlay. This planning begins with a survey of the number of vehicles for 5 working days to get the average daily traffic (LHR), then a survey of data collection of soil bearing capacity using DCP. After all the required data, the pavement thickness calculation is carried out using the 2013 MDP method. Based on the results of these calculations, it was found that the required layers were AC-WC 4 cm and AC-BC 6 cm.